La production animale dans le systeme agro-pastoral du Mali central - Wilson, R.T. (CIPEA, 1981)
Study of livestock production in the agro-pastoral system of Central Mali based on a state of knowledge report of the pastoral & agro-pastoral systems of Mali & on a continuous study of representative herds in both the irrigated rice & rainfed millet sub-systems of the agro-pastoral system. Describes livestock ownership & management in the system & analyzes data on cattle, sheep & goat flock & herd population structures, reproductive performance, weight & growth, offtake & production; with particular reference to intervention possibilities & the application of the computer model to the field data.